An application of the relative warps analysis to problems in human paleontology - with notes on raw data quality - Frieß, Martin (Image analysis and stereology, 2003)
This study investigates the use of geometric morphometrics as well as methodological aspects specifically related to its application in paleoanthropology. Based on lateral photographs taken from a fossil sample of 58 specimens, a relative warps analysis was computed in order to assess the variation of cranial shape among various hominin groups. The fossil sample represents Middle and Late Pleistocene populations commonly assigned to H. erectus, H. neanderthalensis, archaic H. sapiens as well as anatomically modern H. sapiens. The preliminary results indicate that several fossil skullsconsidered as belonging to archaic H. sapiens have a distinct shape compared to modern humans. The results suggest that these hominins are not as closely related to modern humans as previously thought. Instead, their morphometric affinities suggest that they are as distinct from modern humans as are the Neandertals. Methodological aspects, such as raw data accuracy and the use of type 2 and 3 landmarks that are directly related to this type of quantitative analysis and that potentially affect their results, are discussed.
Keywords: Paleontology; Kraniometrija; Lobanja; Skull; Anatomy And Histology; Paleontologija; Hominidae; Slika, obdelava z računalnikom; stereologija; Craniometry; hominidi; Image Processing, Computer-Assisted; anthropology; antropologija